Low Temperature Processed Fully Printed Efficient Planar Structure Carbon Electrode Perovskite Solar Cells and Modules - Yang, Fu; Dong, Lirong; Jang, Dongju; Saparov, Begench; Tam, Kai Cheong; Zhang, Kaicheng; Li, Ning; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2021)
Scalable deposition processes at low temperature are urgently needed for the commercialization of perovskite solar cells (PSCs) as they can decrease the energy payback time of PSCs technology. In this work, a processing protocol is presented for highly efficient and stable planar n–i–p structure PSCs with carbon as the top electrode (carbon-PSCs) fully printed at fairly low temperature by using cheap materials under ambient conditions, thus meeting the requirements for scalable production on an industrial level. High-quality perovskite layers are achieved by using a combinatorial engineering concept, including solvent engineering, additive engineering, and processing engineering. The optimized carbon-PSCs with all layers including electron transport layer, perovskite, hole transport layer, and carbon electrode which are printed under ambient conditions show efficiencies exceeding 18% with enhanced stability, retaining 100% of their initial efficiency after 5000 h in a humid atmosphere. Finally, large-area perovskite modules are successfully obtained and outstanding performance is shown with an efficiency of 15.3% by optimizing the femtosecond laser parameters for the P2 line patterning. These results represent important progress toward fully printed planar carbon electrode perovskite devices as a promising approach for the scaling up and worldwide application of PSCs.
CRIS-Team Scopus Importer:2021-06-18
Keywords: carbon electrodes; doctor blades; fully printed devices; long-term stability; perovskite solar cells